Elements of the Speech Absurd in the Novel “The Meerkat House” by A. Zhaksylykov - Baizhigit, Botagoz Sabitkyzy; Shmakova, Elena Sergeevna; Abdrakhman , Gulnar; Altayeva, Gulnar Abdullovna (Journal of Ecohumanism, 2024)
In the theoretical part of the article, a literary review of the study of the category of the absurd in world and Russian literature is provided. Works by S.A. Kharlamova, V.Yu.charskaya-Boyko, G.M. Kruzhkov, W. Tigges, O.D. Burenina, and L.V. Safronova are considered. The practical part of the article describes elements of speech absurd in the novel “The Meerkat House” by A. Zhaksylykov. During the analysis of the verbal elements of the work, homogeneous enumerations are highlighted as elements of verbal absurdity that reach absurd proportions in the text. One important aspect of the work is the use of the “poetics of error” creating an effect of absurdity and unexpectedness in the text, contributing to the sense of the absurd. A technique of absurdity in the verbal organization of the work is the use of a large number of authorial neologisms in the characters’ speech, which are conditionally divided into several categories in the article. Additionally, the technique of “lexical hybridization” is considered in a comparative aspect in the novel’s text. Apart from identifying absurdity in the verbal organization of the novel, the absurdity of the novel’s characters, space and others are examined. The analysis reveals absurd metaphors and expressions, abbreviations understood only within the context of this novel and a large number of phrases with words like “corn”, “jugarn” and “jubuy”. A. Zhaksylykov employs a classic technique of absurdity, blurring the line between dream and reality, where events in dreams are almost indistinguishable from reality. The novel not only blends the dreams of the narrator but also simultaneously describes the protagonist’s past, his childhood spent in the village, his life in various transformations and more.